2021
DOI: 10.32725/jab.2021.024
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid suppresses inflammation, angiogenesis, and improves paclitaxel induced apoptosis in a breast cancer model via NF3 κB-p53-caspase-3 pathways modulation

Abstract: Rosmarinic acid is a natural polyphenolic compound that is found in different plant species and used for different medicinal purposes. This study aimed to investigate the chemo-preventive effect of rosmarinic acid and evaluate its antitumor efficacy alone or in combination with Paclitaxel in breast cancer mice model. Ehrlich induced mice mammary solid tumor model was used in the study. Mice were treated with oral rosmarinic acid and intraperitoneal Paclitaxel. Inflammation, angiogenesis, and apoptosis were che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…RA exhibited chemo-preventive effects alone and combined with Paclitaxel drug in breast cancer mice models. RA significantly suppressed NF-κB, VEGF, TNF-α expression and restored P53, Bcl-2, Bax, and caspase-3 levels, causing apoptosis (Mahmoud et al 2021 ). Interestingly, in another study, Zhou et al ( 2022 ) reported RA-based reduction in pancreatic ductal adenocarcinoma by restraining Gli translocation and facilitating proteasomal degradation.…”
Section: Clinical Implications Of Ramentioning
confidence: 99%
“…RA exhibited chemo-preventive effects alone and combined with Paclitaxel drug in breast cancer mice models. RA significantly suppressed NF-κB, VEGF, TNF-α expression and restored P53, Bcl-2, Bax, and caspase-3 levels, causing apoptosis (Mahmoud et al 2021 ). Interestingly, in another study, Zhou et al ( 2022 ) reported RA-based reduction in pancreatic ductal adenocarcinoma by restraining Gli translocation and facilitating proteasomal degradation.…”
Section: Clinical Implications Of Ramentioning
confidence: 99%
“…RA induced apoptosis by restoring the expressions of Bcl-2, Bax, and caspase-3. In Ehrlich solid tumor mice, RA, in combination with paclitaxel, significantly decreased the growth of the tumor with enhancement in levels of apoptotic markers ( Mahmoud et al, 2021 ).…”
Section: Cellular and Molecular Mechanisms Of Polyphenols In Cancer: ...mentioning
confidence: 99%
“…The tumor size treated with RA and paclitaxel combination showed a significant reduction. Hence, RA may increase the sensitivity of breast cancer cells to paclitaxel through the NF-κB-p53-caspase-3 pathway ( Mahmoud et al, 2021 ). The synergistic effects of CPT, Sal A, Tan IIA, and RA for breast cancer treatment are shown in Table 1 .…”
Section: Drug Combination Of the Main Compounds In Salvia M...mentioning
confidence: 99%
“…Interestingly, it was demonstrated that RA could dose-dependently inhibit the migration of MDA-MB-231BO bone-homing, MCF-7, MDA-MB-231, and MDA-MB-468 breast cancer cells ( Xu et al, 2010 ; Juskowiak et al, 2018 ; Messeha et al, 2020 ; Yahia Darwish et al, 2020 ). In addition, RA significantly improved the therapeutic effect of paclitaxel in an Ehrlich’s ascites carcinoma suspension-induced breast cancer mouse model ( Mahmoud et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation